In Silico Study: ACE Inhibitory Activity as a Marine Animal Fatty Acid Antihypertensive Candidate - Maharani Dyah Arumsari; Ahmad Misbakhus Sururi; Excelino Hendrata; Rahmadian Kahfi Zulfa Kamila; Dhea Mutiara Fernanda Wibowo; Luluatul Fajriyah; Dwi Anggorowati Rahayu (Jurnal Biodjati, 2024)
Marine life has much potential for development, especially in the medical field. Its main content is fatty acids, where fatty acids have potential as antihypertensive agents. This research aims to determine the potential of the primary fatty acids in marine biota as antihypertensive agents through an in-silico approach using molecular docking. This study uses the Angiotensin Converting Enzyme (ACE) receptor as the target protein and fatty acid ligands (myristic acid, pentadecanoic acid, eicosapentaenoic acid, linoleic acid, vaccenic acid, 11-eicosenoic acid, palmitic acid), and the control drug captopril for comparison. The initial stages of the research include protein and ligand preparation, followed by molecular docking and visualization. Potential compounds were then analyzed with Lipinski drug-likeness and PASSOnline. The research results show that eicosapentaenoic acid and linoleic acid have the potential as ACE inhibitors. PASSOnline predictions indicate that both had a high probability of being vasodilator agents. Therefore, these two fatty acids had the potential as antihypertensive agents. Further research is needed through in vitro and in vivo testing to utilize marine biota in the medical world.